PADANAN TERJEMAHAN SHUUJOSHI YO, ZO, ZE, SA, DAN WA PADA KOMIK DORAEMON VOL.6 - M.Herfiansyah, M.Herfiansyah; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Shuujoshi is particle that show narrator attitude with respect to the associate narrator and event. Shuujoshi gives important role to make conversation become simply natural. Shuujoshi is type of fundamental language expression that are used in human daily activity. This circumstance had made it become interesting in translating process and unique as well. The objective of this research was to describe the translation of ending particle (shuujoshi) from japanese to indonesian language from doraemon comic in japanese language and its translation.The result showed that : 1. There were some of few words that can't be translated according to Shuujoshi translation. 2.The shuujoshi can’t be translated, mean of equivalent can be reached because expression of source language can be used in to target language, but a few word can’t be translated. 3. Shuujoshi translation be related with context of story.Keyword: translation, shuujoshi, eqiuvalent